Endoscopic interventions in tumor of trachea - E. A. Drobyazgin; Yu. V. Chikinev; I. E. Sudovykh; I. V. Peshkova (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The authors assessed possibilities of endoscopic methods for restoration and maintenance of trachea patency. MATERIAL AND METHODS. The article presents results of endoscopic treatment of 26 patients with trachea tumors. Tumor lesions of trachea was the main cause of contraction (primary tracheal cancer had 9 patients; esophageal cancer with invasion inside trachea - 5 patients; relapse of trachea cancer - 1case; relapse of larynx cancer - 1 case; lung cancer with invasion inside trachea - 3 cases; thyroid cancer - 2 patients). RESULTS. Endoscopic interventions were applied in order to restore the trachea patency such as tumor bougienage, electro-excision, tumor cutting, trachea stenting. There was observed bleeding in 3 patients, though it didn’t influence on operation approach. The patency of trachea was restored in all cases. Trachea stenting was performed in 19 patients as a preventive measure (silicone stents in 4 cases; self-expandable metal stent in 15 cases). Medical care remained actual in both restoration and trachea patency supporting. CONCLUSIONS. Endoscopic methods showed the high efficacy in treatment of patients with trachea tumors.